Middle class and welfare state: making sense of an ambivalent relationship - Barbehön, Marlon; Geugjes, Marilena; Haus, Michael (Taylor & Francis Group, 2020)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Acknowledgements -- Introduction -- 1 The middle class: a constructivist perspective -- 2 Middle class within social and political theory: old heritage, contemporary variations -- 3 Middle class and theory of the welfare state: meanings of welfare, overlapping consensus, and target group constructions -- 4 Different welfare regimes, different middle classes: on methodology and methods -- 5 Sweden: the egalitarian understanding of the middle class -- 6 Germany: the conservative-communitarian understanding of the middle class -- 7 United Kingdom: the libertarian-multicultural understanding of the middle class -- 8 Conclusion -- Appendix -- References -- Index.
Description based on publisher supplied metadata and other sources